ANALISIS STRUKTUR MODAL DAN PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN PADA PT FKS FOOD SEJAHTERA TBK PERIODE TAHUN 2013 - 2022 - Zanuba, Iqrima Apik; Mardiana, Sri (Journal of Research and Publication Innovation, 2024)
This study is to determine the Financial Performance of PT FKS Food Sejahtera Tbk for the Period 2013-2022 in terms of Capital Structure and Profitability. This type of research uses descriptive analysis methods with a quantitative approach. Based on the research results, the Capital Structure calculated using the Solvency Ratio, namely the Debt to Asset Ratio obtained an average value of 113.18% declared "Unhealthy", meaning that the company has more debt than assets and the Debt to Equity Ratio obtained an average value of 33.19% declared "Healthy", meaning that the company's equity is able to pay its debts. The company's profitability calculated using the Return On Asset ratio obtained an average value of (12.93%) declared "Unhealthy" and Return On Equity obtained an average value of 28.15% declared "Unhealthy". This means that the company has not been able to manage all assets and equity owned optimally but the company is able to manage cost of goods sold to increase profits.